Immunization against Clostridium perfringens cells elicits protection against Clostridium tetani in mouse model: identification of cross-reactive proteins using proteomic methodologies - Singh Lokendra; Bansod Sunita; Alam Syed (BMC Microbiology, 2008)
Abstract Background Clostridium tetani and Clostridium perfringens are among the medically important clostridial pathogens causing diseases in man and animals. Several homologous open reading frames (ORFs) have been identified in the genomes of the two pathogens by comparative genomic analysis. We tested a likelihood of extensive sharing of common epitopes between homologous proteins of these two medically important pathogens and the possibility of cross-protection using active immunization. Results Eight predominant cross-reactive spots were identified by mass spectrometry and had hits in the C. tetani E88 proteome with significant MOWSE scores. Most of the cross-reactive proteins of C. tetani shared 65–78% sequence similarity with their closest homologues in C. perfringens ATCC13124. Electron transfer flavoprotein beta-subunit (CT3) was the most abundant protein (43.3%), followed by methylaspartate ammonia-lyase (36.8%) and 2-phosphoglycerate dehydratase (35.6%). All the proteins were predicted to be cytoplasmic by PSORT protein localization algorithm. Active immunization with C. perfringens whole cells elicited cross-protective immunity against C. tetani infection in a mouse model. Conclusion Most of the dominant cross-reactive proteins of C. tetani belonged to the cluster of orthologous group (COG) functional category, either of posttranslational modification, protein turnover, and chaperones (O) or energy production and conversion (C). The homologs of the identified proteins have been shown to play role in pathogenesis in other Gram-positive pathogenic bacteria. Our findings provide basis for the search of potential vaccine candidates with broader coverage, encompassing more than one pathogenic clostridial species.